Comparison of renal impairment post-myocardial infarction with reduced and preserved left ventricular function in rats with normal renal function. Issue 1 (1st January 2020) - Wen, Zhuzhi; Mai, Zun; Zhu, Xiaolin; Chen, Yangxin; Geng, Dengfeng; Wang, Jingfeng
Abstract: This study aimed to compare the renal impairments in post-myocardial infarction (MI) rats with normal renal biochemical parameters at baseline with versus without cardiac dysfunction and explore the potential mechanisms involved in these differences. Sprague–Dawley rats with permanent ligation of coronary artery were used as MI models. Renal function, histological and molecular changes were compared between the reduced ejection fraction (EF) (EF < 40%) group and the preserved EF (EF ≥ 40%) group 3 or 9 weeks post-MI. The results revealed that blood cystatin C increased significantly at 9 but not 3 weeks, but it was not associated with cardiac dysfunction. Renal fibrosis and inflammatory cell infiltrations increased significantly in the reduced EF group than in the preserved EF group at 3 and 9 weeks. Glomerular podocyte injury, identified by increased immunostaining for desmin and decreased immunostaining for Wilms' tumor-1, was more significant in the reduced EF group than in the preserved EF group at 9, but not 3 weeks. The number of p16 ink4a -positive and 8-hydroxy-2′-deoxyguanosine-positive podocytes was greater in the reduced EF group than in the preserved EF group at both time points. These changes were associated with increased expression of angiotensin II type 1/2 receptors at both time points. In conclusion, our study demonstrated that cardiac dysfunction accounted for substantially severity in renal parenchymal impairment in a partially time-dependent manner, and local activation of angiotensin II receptors, increased cell senescence and oxidative stress, and enhanced inflammatory reaction may be potential modulators participated in the deterioration of renal parenchymal injury.